Indonesian National Job Qualifications: Literature Review - Tenda, Mirjam Pratidina; Bahri, Efri Syamsul; Lumataw, Jane Arthur (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
The promise of the future can be anticipated by preparing superior and competent human resources. One effort can be made to build standards for developing Indonesian human resources. The Indonesian National Qualifications Framework (KKNI) is used as a reference to recognize work competencies by job structures in various sectors. This research aims to conduct a review of the KKNI. This study uses a qualitative method. The research approach was carried out descriptively, including policy and literature studies. Data comes from regulations, journal articles, and reference books. This research found that the KKNI refers to Presidential Regulation Number 8 of 2012 concerning the Indonesian National Qualifications Framework. The KKNI consists of nine qualification levels, from level 1 as the lowest to level 9) as the highest. The KKNI drafting team needs to use this policy as a reference when preparing the KKNI. The government and strategic stakeholders must continue collaborating to develop superior and competent human resources supported by national programs and budgets.